Optimal Solution For Ocb Improvement Through Strengthening Of Servant Leadership, Creativity, And Empowerment - Hermawan, Andi; Sunaryo, Widodo; Hardhienata, Soewarto (Universitas Pakuan, 2022)
In educational institutions, teachers are a core part of the management element. Teachers who are successful in carrying out the main tasks as stated in their job descriptions coupled with the awareness of doing something extra are the keys to organizational success. Extra activities that are not directly related to the applicable formal reward system are called OCB (Organizational Citizenship Behavior. Based on preliminary research, it is known that PGRI Vocational High School (SMK) teachers in Bogor Regency have relatively low OCB. information on variables related to the increase in OCB. The purpose of this study was to make efforts to increase teacher OCB by conducting research on the relationship between the variables of serving leadership, creativity, and empowerment. This study uses correlational statistical analysis methods to determine the relationship between the variables studied and the SITOREM method for indicator analysis in order to obtain optimal solutions in efforts to increase teacher OCB. There is a positive relationship between empowerment and OCB with a correlation coefficient of ry3 = 0.502 so that strengthening empowerment can increase OCB. From the SITOREM analysis, the optimal solution is obtained that of the 27 indicators there are 14 indicators that are good so that they are maintained or developed and there are 13 indicators that are still weak so that they need to be improved.